1994
DOI: 10.1136/hrt.72.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal hypoxaemia after myocardial infarction: association with nocturnal myocardial ischaemia and arrhythmias.

Abstract: Objective-To document the trend in arterial hypoxaemia and electrocardiographic abnormalities on the second to sixth nights after acute myocardial infarction. Patients-Nineteen consecutive patients with acute myocardial infarction who were monitored continuously during the night (minimum 2300-0700) with a Holter tape recorder and a pulse oximeter. Fifteen patients were monitored for five nights, one patient for four nights, one patient for three nights, and two patients for two nights. Results-Five patients ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…The secondary outcomes of ventricular tachycardia occurrence and use of opiates were not different between the two groups, despite a higher prevalence of severe hypoxaemia in the group receiving air. These findings are consistent with previous studies that reported no relationship between hypoxia and ischaemia in coronary artery disease,36 37 but contrasted with another study that demonstrated a temporal relationship between nocturnal hypoxaemia and both ST-segment depression and arrhythmia after a MI 38…”
Section: Discussionsupporting
confidence: 92%
“…The secondary outcomes of ventricular tachycardia occurrence and use of opiates were not different between the two groups, despite a higher prevalence of severe hypoxaemia in the group receiving air. These findings are consistent with previous studies that reported no relationship between hypoxia and ischaemia in coronary artery disease,36 37 but contrasted with another study that demonstrated a temporal relationship between nocturnal hypoxaemia and both ST-segment depression and arrhythmia after a MI 38…”
Section: Discussionsupporting
confidence: 92%
“…Nocturnal oxygen desaturation in the setting of an unstable coronary syndrome is a proven stimulus for ischaemia and lethal ventricular arrhythmia. 15 Our patients had chronic stable heart failure; none had an unstable coronary syndrome. A single study has reported that CRT reduces the frequency of ICD discharge.…”
Section: Discussionmentioning
confidence: 73%
“…Episodes of hypoxemia after surgery have been reported to occur mostly between postoperative nights 2 to 5. 58,59,65 These episodes may increase the risk of wound infection, cerebral dysfunction, and cardiac arrhythmias. 66 In an observational study at Mayo Clinic, it was found that the incidence of acute myocardial infarction peaked on day 3 after surgery.…”
Section: Sleep In America 2005mentioning
confidence: 99%